Perancangan Vlog Dokumenter Kuliner Di Negara Negara Taiwan - Intan Pratama Putri (Journal of Information System and Technology (JOINT), 2020)
Video is a visual medium that is often used at this time. The more advanced technology the more developments and new things that emerge one of them is a video blog (vlog) which is the development of the blog that is now present in the form of video. Many of the vlogs are documentary vlogs that contain real documentation about a trip or an activity because it is a culinary documentary vlog that informs about the culinary in a region or country. The purpose of this final task design is to facilitate Indonesian tourists who visit Taiwan to see the culinary delights in Taiwan. The research method used in this project is Multimedia Development Life Cycle by utilizing Adobe Premiere Pro CS6 software for editing. The design of this documentary vlog will be a culinary documentary vlog that will be authors uploaded to Youtube. The results obtained after first uploaded video get 132 viewers and 50 like videos running smoothly and in accordance with the design and purpose of providing information to the audience is adding information about Taiwanese culinary.